1998
DOI: 10.1111/j.1600-0765.1998.tb02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Porphyromonas gingivalis and Streptococcus gordonii

Abstract: Confocal scanning laser microscopy (CSLM) was used to visualize and quantify biofilm formation by the oral bacteria Streptococcus gordonii and Porphyromonas gingivalis. A saliva‐coated glass coverslip under continuous bacterial challenge and conditions of low shear force was used to investigate attachment to the salivary pellicle and also the effect of cell‐cell interactions on the extent of colonization and biofilm development. S. gordonii bound to the salivary pellicle and outcompeted P. gingivalis for attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 25 publications
0
18
0
8
Order By: Relevance
“…P. gingivalis adherence to oral streptococci is multimodal and involves at least two distinct sets of adhesins and receptors [27]. In vitro, P. gingivalis adheres avidly to sessile streptococci, and once attached, it rapidly forms a biofilm comprising towering microcolonies separated by fluid-filled channels [28]. S. sanguinis has the ability to generate hydrogen peroxide, which is a key factor in the antagonistic interaction between S. sanguinis and P. gingivalis [29].…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis adherence to oral streptococci is multimodal and involves at least two distinct sets of adhesins and receptors [27]. In vitro, P. gingivalis adheres avidly to sessile streptococci, and once attached, it rapidly forms a biofilm comprising towering microcolonies separated by fluid-filled channels [28]. S. sanguinis has the ability to generate hydrogen peroxide, which is a key factor in the antagonistic interaction between S. sanguinis and P. gingivalis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Genetically distinct oral bacteria have been shown to adhere to tooth enamel and to one another by several specific adhesinreceptor interactions. Research from various groups demonstrated that members of the Streptococcus genus are the early colonizers that anchor the biofilms to saliva-coated substratum in vitro and reflect in vivo biofilm initiation (11,34,35), and, in particular, S. gordonii demonstrates this property (8,17). Intraspecies coaggregation of streptococci has been shown by extensive coaggregation analysis (23); however, in our study, unique sequential deposition of taxonomically related coaggregation partners such as S. gordonii, S. oralis, and S. sanguinis was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Autoclave utilizada para esterilização dos blocos (C) A periodontite apical é a principal patologia associada com o fracasso do tratamento endodôntico, se encontrando nela uma vasta variedade de espécies bacterianas (SKUCAITE et al, 2010;ZIJNGE et al, 2010). No entanto, a maioria dos trabalhos analisa o poder antimicrobiano dos irrigantes endodônticos contra espécies bacterianas isoladas (JACINTO et al, 2003;EICK, SELTMANN, PFISTER, 2004;DUNAVANT et al, 2006;CLEGG et al, 2006;DUGGAN, SEDGLEY, 2007;GIARDINO et al, 2007;OZOK et al, 2007;SEDLACEK, WALKER, 2007;CAMARA et al, 2009;ARIAS-MOLIZ et al, 2010;CHAVEZ DE PAZ, BERGENHOLTZ, SVENSATER, 2010), não permitindo as interações bacterianas características dos biofilmes multi-espécie que os fazem mais resistentes (COOK, COSTERTON, LAMONT, 1998;STANDAR et al, 2010;ZIJNGE et al, 2010).…”
Section: Dados Curricularesunclassified
“…Os estudos in vitro são muito importantes para determinar as interações bacterianas que ocorrem em um biofilme (KOLENBRANDER et al, 1993;COOK;LAMONT, 1998;PALMER et al, 2001;DIAZ et al, 2006;STANDAR et al, 2010), mas não são capazes de simular de uma forma exata as condições de crescimento bacteriano na boca, como por exemplo, a diversidade de nutrientes, mudanças de humidade e pH, temperatura, saliva; etc.…”
Section: Da Metodologiaunclassified